2012
DOI: 10.1039/c2ob25774b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of a new triazole–oxotechnetium complex

Abstract: A new triazole oxotechnetium chelating agent was synthesized via a 'Click-to-Chelate' strategy. In vivo evaluation of the corresponding (99m)Tc complex shows that the tracer exhibits very interesting properties for molecular imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…S-triphenylmethyl-thioglycolic acid (T A -trityl) was prepared by a modification of the procedure on Martinage et al [36]. Briefly, 1.5 g (5.77 mmol) of triphenylmethanol was added to a 25 mL TFA solution of thioglycolic acid (400 µL, 5.77 mmol) and stirred for 5 h under argon at room temperature.…”
Section: Preparation Of S-triphenylmethyl-thioglycolic Acidmentioning
confidence: 99%
“…S-triphenylmethyl-thioglycolic acid (T A -trityl) was prepared by a modification of the procedure on Martinage et al [36]. Briefly, 1.5 g (5.77 mmol) of triphenylmethanol was added to a 25 mL TFA solution of thioglycolic acid (400 µL, 5.77 mmol) and stirred for 5 h under argon at room temperature.…”
Section: Preparation Of S-triphenylmethyl-thioglycolic Acidmentioning
confidence: 99%
“…Thus, we anticipated that neutral technetium or rhenium complexes based on triazole chelating systems could exhibit in vivo stabilities similar to those obtained with pyridine chelating analogues. Martinage et al ([TcO] 3+ core) and our preliminary study ([Tc(CO) 3 ] + core) demonstrated the feasibility of developing in vivo stable technetium‐99m complexes , . We then decided to continue our investigations with rhenium(I) with a view to developing new therapeutic tools based on rhenium‐188 (half‐life of 16.9 h, β‐emitter, E = 2.12 MeV).…”
Section: Introductionmentioning
confidence: 97%
“…Martinage et al ([TcO] 3+ core) and our preliminary study ([Tc(CO) 3 ] + core) demonstrated the feasibility of developing in vivo stable technetium-99m complexes. [10,13] We then decided to continue our investigations with rhenium(I) with a view to developing new therapeutic tools based on rhenium-188 (half-life of 16.9 h,emitter, E = 2.12 MeV). To the best of our knowledge, only one example of the rhenium-188 radiolabelling of a chelator containing a triazolyl ring has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Bearing that in mind, we anticipated that the formation, using a two‐steps click‐to‐chelate strategy, of a semi‐rigid chelating system containing an aromatic backbone and the triazole unit, should lead in a few steps and with high yield to the corresponding very stable Tc(CO) 3 ‐complex. Even though any semi‐rigid ligand has yet been synthesized, the conception of pre‐organized chelating systems using a click‐to‐chelate approach have been recently highlighted for the preparation of new triazole‐oxotechnetium complexes . So in this paper, we described a simple, rapid, and convenient synthetic route for the first 99m Tc(I)‐specific semi‐rigid tridentate click ligand, which incorporates the design features illustrated in Scheme ; these include the following: (i) a methyl carboxylate arm directly connected at the N1 position of the five‐membered triazole ring as potential bioconjugation site and (ii) a N 2 O tridentate chelating system combining the 1,2,3‐triazole moiety with 2‐aminophenol derivative.…”
Section: Introductionmentioning
confidence: 99%